Hating the cute kitten or loving the aggressive pit-bull: EC effects depend on CS-US relations - Förderer, Sabine; Unkelbach, Christian (Cognition & emotion, 2012)
Evaluative conditioning (EC) refers to valence changes of initially neutral stimuli (CSs) through repeated pairings with positive or negative stimuli (USs). The current study is about the moderating role of qualifiers that specify the CS-US relation during these pairings. We show successful EC with pictures of men (CSs) and of liked/disliked animals or landscapes (USs). More importantly, the same pairings resulted in standard and reversed EC effects depending on semantic qualifier of the CS-US relation. CSs loving positive (negative) USs became more positive (negative), while CSs loathing positive (negative) USs became more negative (positive). These data favour a propositional EC account (De Houwer, 2009) over a purely associative account, as they show that it is not only relevant that CS and US are related, but how they are related.